Perception of School Nurses in Saudi Arabia - Yasin, Hala Mohammed; Pera, Pilar Isla; Mujallad, Alaa Fouad; Matheu, Carmen López (Journal of medical and pharmaceutical sciences, 2023)
In Saudi Arabia, the school nurse exists only in private schools. The aim of this qualitative study is to identify the factors that hinder the implantation of a school nurse figure in Jeddah, Saudi Arabia through exploring the perspectives of 21 participants including directors, teachers, and parents about the school nurses, and find out what they think about the role of the nurse in a school environment using in-depth individual interviews method. The findings confirmed the need for school nurse in both private and public schools in Saudi Arabia. All the information considers that the school nurse has a positive impact on students, teachers, and families. The problems that hinder the inclusion of the school nurse in public schools are structural.
Keywords: Nursing; school nurse; Saudi Arabia